Modified silicon electrode, preparation thereof and application of modified silicon electrode in solid-state battery
Through the two-stage modification method, the structural stability and interface effect of the silicon negative electrode in solid-state batteries are improved, and the problems of volume expansion, short cycle life and poor interface stability are solved, and long-range cycle stability and wide temperature domain adaptability are achieved.
Patent Information
- Application Number
- CN202411691783.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The silicon negative electrode has problems such as volume expansion, short cycle life and poor interface stability in solid-state batteries, making it difficult to adapt to the long-term stable cycle and wide-temperature structure stability requirements of solid-state batteries.
Using the two-stage modification process method, the nano-silicon material is first placed in the modified liquid A for the first modification process to form modified silicon particles, and then combined with the binder on the negative current collector, and the second modification process is performed. The modified liquid B is subjected to ultrasonic assisted treatment under light irradiation to form the modified silicon negative electrode.
The structural stability and interface effect of the silicon negative electrode in solid-state batteries are significantly improved, the long-range cycle stability and wide temperature domain adaptability of the battery are improved, and good electrochemical performance in the range of -35℃~75℃ is achieved.
Smart Images

Figure CN119764341A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of solid electrode negative electrode preparation, and specifically relates to a new silicon electrode for long-life solid battery. Background Art
[0002] Solid-state batteries use solid electrolytes and have the potential for high energy density, long life, fast charging capability, and safety. Compared with traditional lithium-ion batteries, solid-state batteries use solid electrolytes instead of liquid electrolytes, which can significantly reduce the risk of leakage and combustion and improve the stability and safety of the battery. In addition, solid-state batteries perform better in low-temperature environments and are more adaptable to temperature changes. These characteristics make solid-state batteries have broad application prospects in electric vehicles, wearable devices, portable electronics, and large-scale energy storage systems. With the deepening of research and the advancement of technology, solid-state batteries are expected to become an important part of the next generation of energy storage technology.
[0003] In order to realize the performance potential of solid batteries, new positive and negative electrode materials need to be matched. The graphite negative electrode material used in traditional lithium-ion batteries has approached its theoretical capacity limit, so finding new negative electrode materials has become the key to the advancement of battery technology. Silicon, as a negative electrode material, has received widespread attention because of its higher theoretical specific capacity than graphite (about 3579mAh / g, more than ten times that of graphite). The combination of silicon negative electrode and solid electrolyte is not only expected to solve the volume expansion problem of silicon negative electrode, but also may achieve a significant improvement in battery performance, opening up a new path for the development of next-generation battery technology. Therefore, the research on silicon negative electrode of solid-state batteries not only has important academic value, but also has huge application potential.
[0004] The current problems with silicon anodes in solid-state batteries mainly include volume expansion of silicon materials, short cycle life, and poor interface stability. Silicon undergoes significant volume changes during the charge and discharge process, which can lead to damage to the electrode structure and a decrease in battery performance. In addition, the interface reaction between the silicon anode and the solid electrolyte may cause an increase in interface impedance, affecting the cycle stability of the battery. These problems need to be solved through innovations in materials engineering and battery design.
[0005] With the development of technology, the prior art also discloses some improved silicon negative electrode solid-state battery technologies. For example, the Chinese patent document with publication number CN116417587A discloses a silicon negative electrode material for all-solid-state lithium-ion battery and its preparation method and application. The silicon negative electrode material for all-solid-state lithium-ion battery includes: a micron silicon material body, a nano silicon material coated on the surface of the micron silicon material body, and a polymer binder bonded between the micron silicon material body and the nano silicon material. For another example, the Chinese patent document with publication number CN117080390A discloses a method for preparing a silicon negative electrode material coated with a solid electrolyte layer, comprising the following steps: placing lithium carbonate and an organic polymer monomer in an inert solvent for solvothermal reaction, and the organic polymer monomer undergoes a ring-opening reaction to generate a mixture A containing an oligoether polymer; dissolving an organic solid electrolyte and a lithium salt in an organic solvent to obtain a solution B; mixing and stirring the mixture A, the solution B and the silicon negative electrode particles evenly, and spray drying to obtain a silicon negative electrode material coated with a solid electrolyte layer.
[0006] Although existing technologies can improve the performance of silicon negative electrodes in solid-state electrolytes to a certain extent, it is still difficult to effectively solve its expansion problem in solid-state battery systems, and it is still difficult to adapt to the long-term stable cycle of solid-state batteries and the structural stability requirements over a wide temperature range. Summary of the invention
[0007] In order to solve the problem that when silicon negative electrode is used in solid-state batteries, its huge volume expansion causes electrode structure destruction and separation from the electrolyte causes performance degradation, the present invention provides a preparation method of modified silicon electrode, aiming to improve its adaptability to solid-state batteries, thereby improving the electrochemical properties of the assembled solid-state battery, such as long cycle and wide temperature range.
[0008] The second purpose of the present invention is to provide a modified silicon electrode obtained by the preparation method and its application in solid-state batteries.
[0009] The third object of the present invention is to provide a solid-state battery comprising the modified silicon negative electrode.
[0010] Due to its huge expansion and powdering and low conductivity, the silicon negative electrode is difficult to adapt to the long cycle and ultra-wide temperature range application requirements of solid-state batteries. In view of this problem, the present invention has provided the following improvement scheme after in-depth research:
[0011] A method for preparing a modified silicon negative electrode, comprising placing a nano-silicon material in a modification liquid A for a first modification treatment to obtain modified silicon particles; the modification liquid A is a solution in which polypropylene carbonate is dissolved;
[0012] The modified silicon particles and the binder are slurried and then composited on the negative electrode current collector to form a silicon negative electrode layer on the negative electrode current collector to obtain a silicon negative electrode;
[0013] Compounding the modified solution B on the silicon negative electrode layer of the silicon negative electrode, and then performing a second stage modification treatment under light irradiation to obtain the modified silicon negative electrode;
[0014] The modified solution B comprises formula 1, formula 2, formula 3 and lithium salt;
[0015]
[0016] The R1 and R2 are independently H or alkyl;
[0017] The R3 is an alkyl group or a substituted alkyl group;
[0018] The R4 is a hydroxyalkyl group or a hydroxy-substituted aryl group;
[0019] Ar1 and Ar2 are independently aryl or substituted aryl, and R is alkyl, alkoxy or aryl;
[0020] The substituents in the substituted alkyl and substituted aryl groups include at least one of phenyl, ether, ester and hydroxyl groups.
[0021] The present invention innovatively uses modification liquid A to perform the first stage modification on nano-silicon in advance, and then uses modification liquid B to perform the second stage modification after it is formed into a silicon electrode. In this way, based on the chemical bridging and physicochemical modification characteristics between the first stage modification and the second stage modification, the adaptability of the modified silicon negative electrode to the solid-state battery can be improved, which helps to improve the structural stability of the prepared modified silicon negative electrode in the solid-state battery, improves the interface effect, and thus helps to significantly improve the electrochemical performance of the solid-state battery, especially helps to improve its long-range cycle and wide temperature range stability.
[0022] In the present invention, the D50 of the nano-silicon material is 50-200nm.
[0023] In the present invention, the solvent in the modified liquid A is a solvent that can dissolve the polypropylene carbonate, such as acetone. There is no special requirement for the content of the polypropylene carbonate in the modified liquid A.
[0024] Preferably, the weight ratio of the nano-silicon material to polypropylene carbonate is 100:0.5-2.
[0025] The present invention can prepare a silicon negative electrode from the modified silicon material based on conventional means.
[0026] For example, the modified silicon material can be dispersed into a slurry using a solvent, and then coated on a conventional negative electrode current collector (such as copper foil), and then dried to obtain the silicon negative electrode.
[0027] The binder includes at least one of PVDF, CMC, SBR and PAA.
[0028] Preferably, the weight ratio of the modified silicon particles to the binder is 80-98:1-5.
[0029] Preferably, a conductive agent is further added to the slurry, wherein the weight ratio of the modified silicon particles to the conductive agent is 80 to 98:1 to 10. The conductive agent may be a component known in the industry, for example, a carbon-based conductive agent such as conductive carbon black.
[0030] In the present invention, on the basis of the first stage modification, a second stage modification is further performed, so that based on the physicochemical reaction between the two stages modification, the adaptability of the prepared silicon negative electrode in the solid-state battery can be improved and its long-term stability can be improved.
[0031] In the present invention, the formula 1 is formula 1a;
[0032]
[0033] Formula 2 is Formula 2a;
[0034]
[0035] In formula 3, the aryl group is a phenyl group or an alkyl-substituted phenyl group;
[0036] Further preferably, the formula 3 is a compound of formula 3a;
[0037]
[0038] In formula 3a, R is ethoxy or phenyl;
[0039] Preferably, the lithium salt includes at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate), and lithium bis(fluorosulfonyl)imide.
[0040] In the present invention, in the modified solution B, the mass ratio of the formula 1, formula 2, formula 3 and the lithium salt is 60-80:15-35:1-5:10-30; preferably 70-75:20-25:3-4:15-20.
[0041] In the present invention, the modified solution B is compounded on the silicon negative electrode layer of the silicon negative electrode by means of scraping or spin coating;
[0042] Preferably, the wavelength of the light irradiation is 200-300 nm.
[0043] Preferably, the power of the light irradiation is 500-5000W, and further can be 900-1100W.
[0044] Preferably, the light irradiation time is 5 to 30 minutes, and further can be 10 to 20 minutes.
[0045] In the present invention, ultrasound assistance is performed simultaneously during the light irradiation process. The present invention's research shows that light irradiation under the preferred ultrasound assistance helps to further optimize the surface structure and the bridging effect of the layers, and helps to further enhance the long-range cycle performance of the prepared silicon negative electrode in the solid-state battery system.
[0046] Preferably, the frequency of ultrasound is 50-80 kHz, and the power is 3.5-8.5 w / cm2.
[0047] The invention also provides a modified silicon negative electrode prepared by the preparation method.
[0048] The present invention also provides an application of the modified silicon negative electrode prepared by the preparation method in the preparation of a solid-state battery.
[0049] The present invention also provides a solid-state battery, which comprises a modified silicon negative electrode prepared by the preparation method of the present invention.
[0050] Beneficial Effects
[0051] The present invention is innovatively based on the first-stage modification, the second-stage modification and the combined operation of the modified components, so that synergy can be achieved. Based on the physicochemical characteristics of the two-stage modification and the chemical reaction between the two-stage modification, the adaptability of the prepared silicon negative electrode in the solid-state battery can be enhanced, thereby improving its long-range cycle stability in the solid-state battery system, and achieving good operation of the battery in a wide temperature range of -35°C to 75°C. DETAILED DESCRIPTION
[0052] The present invention will be described in detail below with reference to the embodiments, but the present invention is not limited thereto.
[0053] In the present invention, the raw materials are all common commercial raw materials known in the battery field. For example, the molecular weight of the polypropylene carbonate can be 30,000 to 60,000.
[0054] Example 1
[0055] Step 1: Dissolve polypropylene carbonate in acetone solution, then stir with nano-silicon (D50 is 105±5nm), the mass ratio of polypropylene carbonate to nano-silicon is 1:100, and after stirring evenly, evaporate the acetone at 60°C to obtain a modified nano-silicon.
[0056] Step 2: A section of modified nano-silicon is used as an electrode active material, mixed with a binder (CMC) and a conductive agent to form a slurry, and then coated on a copper foil and dried to obtain a nano-silicon electrode, wherein the weight ratio of the section of modified nano-silicon: CMC: SBR: Super C is 90:3.5:3:3.5.
[0057] Step 3: Formula 1a, Formula 2a, Formula 3aa (Formula 3a where R is phenyl), and lithium bis(trifluoromethanesulfonyl)imide are mixed evenly in a mass ratio of 70:20:3:20 to prepare a modified liquid B, and then the nano-silicon electrode is used as a substrate, the precursor liquid is poured on the surface and scraped flat with a scraper, and then irradiated with a 200-300nm wavelength, 1000±50W ultraviolet lamp for 10-15 minutes to obtain the desired long-life solid battery silicon electrode.
[0058] Example 2
[0059] Compared with Example 1, the only difference is that in step 1, the mass ratio of polypropylene carbonate to nano silicon is 1.5:100; in step 2, the weight ratio of first-stage modified nano silicon: CMC: SBR: Super C is 90:4:3:3. Other operations and parameters are the same as in Example 1.
[0060] Example 3
[0061] Compared with Example 1, the only difference is that the mass ratio of Formula 1a, Formula 2a, Formula 3aa (Formula 3a where R is phenyl) and lithium bistrifluoromethanesulfonyl imide is 75:25:4:15. Other operations and parameters are the same as in Example 1.
[0062] Example 4
[0063] Compared with Example 1, the only difference is that the irradiation process in step 3 is carried out under an ultrasonic field, wherein the frequency of the ultrasound is 60-70 kHz and the power is 5-5.5 w / cm2. Other operations and parameters are the same as those in Example 1.
[0064] Comparative Example 1
[0065] Compared with Example 1, the only difference is that step 1 is not performed, and the nano-silicon is directly subjected to step 2 and subsequent treatments. Other operations and parameters are the same as those in Example 1.
[0066] Comparative Example 2
[0067] Compared with Example 1, the only difference is that in step 1, polyacrylic acid is used to replace the polypropylene carbonate, and other operations and parameters are the same as in Example 1.
[0068] Comparative Example 3
[0069] Compared with Example 1, the only difference is that in step 3, Formula 2a is not added, and other operations and parameters are the same as in Example 1.
[0070] Comparative Example 4
[0071] Compared with Example 1, the only difference is that in step 3, a comparative compound is used. ) replaces the formula 2a, and other operations and parameters are the same as those in Example 1.
[0072] Comparative Example 5
[0073] Compared with Example 1, the only difference is that the modified liquid B of step 3 is added in step 1, and in step 3, the modified liquid B is no longer added, that is, in step 1, the modified liquid B of step 3 is added to the modified liquid A, and the treatment of step 1 is performed, followed by the treatment of step 2, and then the light treatment of step 3 is performed. Other operations and parameters are the same as in Example 1.
[0074] The prepared silicon negative electrode sheet and the lithium sheet are directly assembled into a fully solid-state half-cell (the silicon layer of the silicon negative electrode is facing the lithium sheet negative electrode). Then the half-cell is subjected to charge and discharge tests at 25°C, -35°C and 75°C, respectively, with a test rate of 0.2C and a voltage range of 0.05-1.5V.
[0075] Test results table 1:
[0076] Table 1
[0077]
[0078] As can be seen from Table 1, based on the first stage modification, the second stage modification and the joint operation of the modified components, synergy can be achieved. Based on the physicochemical characteristics of the second stage modification and the chemical reaction between the two stages of modification, the adaptability of the prepared silicon negative electrode in the solid-state battery can be enhanced, thereby improving its long-term cycle stability in the solid-state battery system, and achieving good operation of the battery in a wide temperature range of -35°C to 75°C. In particular, light irradiation under the assistance of ultrasound is helpful to further optimize the interface structure and further enhance the long cycle and ultra-low and ultra-high temperature adaptability of the prepared silicon negative electrode.
Claims
1. A method for preparing a modified silicon negative electrode, characterized in that: Placing the nano-silicon material in a modification liquid A for a first modification treatment to obtain modified silicon particles; the modification liquid A is a solution containing polypropylene carbonate; The modified silicon particles and the binder are slurried and then composited on the negative electrode current collector to form a silicon negative electrode layer on the negative electrode current collector to obtain a silicon negative electrode; Compounding the modified solution B on the silicon negative electrode layer of the silicon negative electrode, and then performing a second stage modification treatment under light irradiation to obtain the modified silicon negative electrode; The modified solution B comprises formula 1, formula 2, formula 3 and lithium salt; The R1 and R2 are independently H or alkyl; The R3 is an alkyl group or a substituted alkyl group; The R4 is a hydroxyalkyl group or a hydroxy-substituted aryl group; Ar1 and Ar2 are independently aryl or substituted aryl, and R is alkyl, alkoxy or aryl; The substituents in the substituted alkyl and substituted aryl groups include at least one of phenyl, ether, ester and hydroxyl groups.
2. The method for preparing a modified silicon negative electrode according to claim 1, characterized in that: The D50 of the nano-silicon material is 50-200nm; Preferably, the weight ratio of the nano-silicon material to polypropylene carbonate is 100:0.5-2.
3. The method for preparing a modified silicon negative electrode according to claim 1, characterized in that: The binder includes at least one of PVDF, CMC, SBR and PAA; Preferably, the weight ratio of modified silicon particles to binder is 80-98:1-5; Preferably, a conductive agent is further added to the slurry, wherein the weight ratio of the modified silicon particles to the conductive agent is 80-98:1-10.
4. The method for preparing a modified silicon negative electrode according to claim 1, characterized in that: The formula 1 is formula 1a; Formula 2 is Formula 2a; In formula 3, the aryl group is a phenyl group or an alkyl-substituted phenyl group; Further preferably, the formula 3 is a compound of formula 3a; In formula 3a, R is ethoxy or phenyl; Preferably, the lithium salt includes at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate), and lithium bis(fluorosulfonyl)imide.
5. The method for preparing a modified silicon negative electrode according to claim 1, characterized in that: In the modified solution B, the mass ratio of the formula 1, formula 2, formula 3 and the lithium salt is 60-80:15-35:1-5:10-30; preferably 70-75:20-25:3-4:15-20.
6. The method for preparing a modified silicon negative electrode according to claim 1, 4 or 5, characterized in that: The modified liquid B is compounded on the silicon negative electrode layer of the silicon negative electrode by means of scraping or spin coating; Preferably, the wavelength of the light irradiation is 200 to 300 nm; Preferably, the power of light irradiation is 500-5000W; Preferably, the light irradiation time is 5 to 30 minutes.
7. The method for preparing a modified silicon negative electrode according to claim 6, characterized in that: Ultrasound assistance is performed simultaneously during the light irradiation process; Preferably, the frequency of ultrasound is 50-80 kHz, and the power is 3.5-8.5 w / cm2.
8. A modified silicon negative electrode obtained by the preparation method according to any one of claims 1 to 7.
9. Use of a modified silicon negative electrode prepared by the preparation method according to any one of claims 1 to 7 in the preparation of a solid-state battery.
10. A solid-state battery, characterized in that: A modified silicon negative electrode prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Oxygen-enriched polymer electrolyte as well as preparation method and application thereof
CN109755643A
Modified silicon-based material as well as preparation method and application thereof
CN111952574A
Battery pre-lithiation slurry, battery negative plate and lithium ion battery
CN114388790A
Negative pole piece and metal lithium battery
CN114512674A
Preparation method of silicon-carbon negative electrode of high-performance lithium ion battery
CN116072826A